Defending behaviors, bullying roles, and their associations with mental health in junior high school students: a population-based study - Wen-Chi Wu; Shyuemeng Luu; Dih-Ling Luh (BMC, 2016)
Abstract Background Students should be encouraged to help prevent or stop bullying. However, defending victims of bullying can impact on mental health. It is not only bystanders who may defend victims, but bullies, victims and bully-victims can also have defending behaviors. Nevertheless, most studies of defending behaviors have been limited to an examination of the reactions of bystanders or those not involved in bullying and have ignored the other players. The aim of this study is to investigate the associations between defending behaviors and mental health among bullies, victims, bully-victims and bystanders. Methods Associations among defending behaviors, mental health (including depressive symptoms and social anxiety), and bullying experiences were cross-sectionally examined in 3441 students (13-15 years old.) from 20 randomly selected junior high schools in Taiwan using a self-report questionnaire. SAS 9.3 Survey Analysis procedures were used to conduct descriptive analysis and multiple regression models. Results Defending behaviors were associated with bullying roles and were higher in victims than in bullies or bystanders. Defending behaviors were positively associated with social anxiety and depressive symptoms. After stratifying by bullying roles, defending behaviors were positively associated with social anxiety in bystanders, and were positively associated with depressive symptoms in victims and bystanders. However, defending behaviors were not significantly associated with mental health indicators in bullies. Conclusions The associations between defending behaviors and mental health varied according to bullying roles. The results suggest that bystanders and victims experience more mental health effects than bullies. Intervention programs aimed at preventing bullying should focus on strategies that minimize social anxiety and depression in victims and bystanders, and urge students to help vulnerable peers during bullying events.